Marketing Strategy and Business Model Canvas at Jeeva Works Corporation - Abdul Karim Ambari; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2020)
One of the community needs especially for men is appropriate barbershop services desired haircut also suitable service time and attractive facilities. The existing barbershop has limitations in facilitating the haircut and desired customer over appropriate service time. Barbershop who can give service according to the hairstyle the customer need and the time that can be determined customers themselves are a new business model in Indonesia and in need business development. Jeeva Works Corporation is developing for facilitate customer needs by providing re-model and registration application technology supported by a hangout facility in the form of coffee shop. Barbershop with combination coffee shop gave birth to the trademark Jeeva Barber Coffee.